The Protective Role of Caring Parenting Styles in Adolescent Bullying Victimization: The Effects of Family Function and Constructive Conflict Resolution - Haoliang Zhu; Haojie Fu; Haiyan Liu; Bin Wang; Xiao Zhong (Behavioral Sciences)
Based on attachment theory and the McMaster family functioning model, this study explores the protective role and mechanisms of a caring parenting style in protecting adolescents from bullying, from the perspective of the family environment. Study 1, conducted in Southwest China with middle school students (n = 4582), investigates the relationship between a caring parenting style and adolescent bullying victimization through a large-scale cross-sectional survey. The results show that both parents’ caring parenting styles are significantly negatively correlated with adolescent bullying victimization. Study 2, a two-wave study (n = 302), explores the protective mechanisms of a caring parenting style in adolescent bullying victimization. We not only observed again that a caring parenting style significantly negatively predicts bullying victimization but also found that family functioning and constructive conflict resolution play a chain-mediating role in this relationship. This finding not only supports the core hypothesis of attachment theory regarding the role of a secure base but also expands the theoretical model of bullying protection from a family ecological perspective by revealing a three-level transmission mechanism of parenting style–family system–individual capability, providing a theoretical anchor for the construction of a “family–school” collaborative intervention framework.